Photodynamic Therapy for the Treatment of Fungal Infections - Wu X; Hu Y (Infection and Drug Resistance, 2022)
Xuelin Wu,1,2 Yongxuan Hu1,2 1Department of Dermatology and Venereology, The Third Affiliated Hospital of Southern Medical University, Guangzhou, People’s Republic of China; 2Guangdong Provincial Key Laboratory of Bone and Joint Degeneration Diseases, Guangzhou, People’s Republic of ChinaCorrespondence: Yongxuan Hu, Department of Dermatology and Venereology, The Third Affiliated Hospital of Southern Medical University, 183 West Zhongshan Road, Guangzhou, People’s Republic of China, Tel + 86 20 62784560, Email huyongxuan2003@163.comAbstract: Cutaneous fungal infections are common in humans and are associated with significant physical and psychological distress to patients. Although conventional topical and/or oral anti-fungal medications are commonly recommended treatments, drug resistance has emerged as a significant concern in this patient population, and safer, more efficacious, and cost-effective alternatives are warranted. Recent studies have reported effectiveness of photodynamic therapy (PDT) against fungal infections without severe adverse effects. In this review, we briefly discuss the mechanisms underlying PDT, current progress, adverse effects, and limitations of this treatment in the management of superficial and deep fungal infections.Keywords: photodynamic therapy, fungal infection, review